Capitalist critique of Karl Marx on surplus value - Gerald Kelvin Onuoha; Ishmael U Gwunireama (Center for Humanities and Innovation Studies, 2022)
Karl Marx (1818–1883) was an outstanding German philosopher of political economy. His disdain and displeasure for capitalism as an economic and political system logically stems from his claim that it is unjustifiably exploitative, dehumanizing, and alienating. He conceives of it as being characterised by wage labor, and this leads to industrial disharmony between the capitalists and the laborers. This paper examines Marx’s conception of surplus value, the nature and character of labour theory of value, and alienation, which are key issues in Marxist-Leninist political philosophy. It is, particularly, a reaction to the Marxian claim that surplus value is created in the course of production. It argues that profit and extra capital are the basis for the survival of many businesses. Therefore, it concludes that what Marx refers to as surplus value actually is a return on investment that the capitalist further puts back into the business to enable the equipment, payment of wages, salaries, and delivery of welfare packages/incentives to workers in order to make a business a going concern. As a result, there is no surplus value, and it is not a valid basis for industrial disharmony between capitalists and laborers as long as the parties are bound by the employment contract negotiated in accordance with the legal regime.